Self‐control and health‐related behaviour: The role of implicit self‐control, trait self‐control, and lay beliefs in self‐control - Hagger, Martin S.; Gucciardi, Daniel F.; Turrell, Amelia S.; Hamilton, Kyra (British journal of health psychology, 2019)
Objectives We tested unique contribution of trait self‐control, implicit self‐control, and lay beliefs in self‐control beliefs to the prediction of health‐related behaviours. We also tested whether relations between trait self‐control and health‐related behaviour, and between implicit self‐control and health‐related behaviours, were moderated by self‐control beliefs. Design Cross‐sectional, correlational. Methods Students (N = 176) completed self‐report measures of trait self‐control, lay beliefs that self‐control is limited or non‐limited, non‐planning, participation in health‐related behaviours (impulsive eating, impulsive drinking, exercise avoidance, watching diet, alcohol consumption, physical activity participation), and demographic variables. Participants also completed a measure of implicit self‐control using an implicit association test. Results Analyses indicated significant negative relations between implicit self‐control and impulsive drinking and alcohol consumption. We also found a positive relationship between implicit self‐control and exercise behaviour, and a negative relationship between implicit self‐control and impulsive eating, both of which fell marginally short of statistical significance. Trait self‐control significantly predicted all behavioural measures and attenuated relations between implicit self‐control and health‐related behaviour. We found no relations between lay beliefs in self‐control and health‐related behaviour. Moderated path analyses revealed that lay beliefs in self‐control moderated relations between trait self‐control and impulsive drinking, implicit self‐control and exercise avoidance, and implicit self‐control and physical activity participation. Conclusions Findings suggest that trait self‐control was a consistent correlate of health‐related behaviour, while the effect sizes of relationships between implicit self‐control and health‐related behaviours were small. Strength of relations between trait self‐control and health‐related behaviours may depend on whether or not individuals believe self‐control is limited. Statement of contribution What is already known on this subject? Self‐control represents individuals capacity to override impulses, break habits, and avoid temptations. Trait self‐control is consistently and positively related to uptake of health‐promoting behaviours (e.g., physical activity, healthy eating). Trait self‐control is consistently and negatively related to health‐compromising behaviours (e.g., alcohol consumption, unhealthy snacking). What does this study add? Proposes that self‐control can also be measured implicitly, beyond individuals’ awareness. Examined effects of implicit measures of self‐control and self‐reported trait self‐control on multiple health behaviours. Effects of implicit self‐control on health behaviours were small and subsumed by trait self‐control. Effects of lay beliefs in self‐control moderated effects of implicit and trait self‐control on some health behaviours.